Dermal drug delivery : from innovation to production - Ghosh, Tapash K. (Boca Raton : CRC Press, Taylor & Francis Group, 2020)
With the continued advancement of better-quality control and patient outcome reporting systems, changes in the development, control, and regulation of all pharmaceutical delivery systems including transdermal and topical products have been happening on a continuous basis. In light of various quality issues that have been reported by patients and practitioners resulting in the recall or removal of products from the market, both the pharmaceutical industries and regulatory agencies have been adopting new measures to address these issues. With chapters written by experts in this field, this book takes a 21st century multidisciplinary and cross-functional look at these dosage forms to improve the development, design, manufacturing, quality, clinical performance, safety, and regulation of these products. This book offers a wealth of up-to-date information organized in a logical sequence corresponding to various stages of research, development, and commercialization of dermal drug delivery products. The authors have been carefully selected from different sectors of pharmaceutical science for their expertise in their selected areas to present objectively a balanced view of the current state of these products development and commercialization via regulatory approval. Their insights will provide useful information to others to ensure the successful development of the next generation dermal drug products. Key Features: Presents current advancements including new technologies of transdermal and topical dosage forms. Presents challenges in the development of the new generation of transdermal and topical dosage forms. Introduces new technologies and QbD (quality by design) aspects of manufacturing and control strategies. Includes new perspectives on pre-clinical and clinical development, regulatory considerations, safety and quality. Discusses regulatory challenges, gaps, and future considerations for dermal drug delivery systems.
Chapter 1 Dermal and Transdermal Drug Delivery Systems: An Overview and Recent Advancements Kenneth A Walters & Majella E Lane Chapter 2 Preclinical and Clinical Safety and Assessment of Transdermal and Topical Dermatological Products Lindsey C. Yeh & Howard I. Maibach Chapter 3 Selection considerations for membranes and models for in-vitro/ex-vivo permeation studies Pei-Chin Tsai, Tannaz Ramezanli, Dina Wadie, Sonia Trehan, Nathaly Martos, Zheng Zhang, Bozena Michniak-Kohn Chapter 4 Design, Development, Manufacturing and Testing of Transdermal Drug Delivery Systems Timothy A. Peterson, Steven M. Wick & Chan Ko Chapter 5 Quality by Design (QbD) principles in the development of Transdermal Drug Delivery Products Muralikrishnan Angamuthu, H.N. Shivakumar & S. Narasimha Murthy Chapter 6 Microneedles for Drug Delivery: Industrial and Regulatory Perspectives Lisa A. Dick, Dan M. Dohmeier, Ann M. Purrington & Scott A. Burton Chapter 7 Biopharmaceutics Aspects of Dermally Applied Drug Delivery Systems Tapash Ghosh Chapter 8 Quality and Performance Tests for Dermal Drug Delivery Systems Margareth R.C. Marques, Tony Bennett & Gregory Fieldson Chapter 9 Perspective on Clinical Trials for Dermal Drug Delivery Systems John T. Farrar & Shamir Kalaria Chapter 10 Regulatory Standards for Approval of Topical Dermatological Drug Products April C. Braddy & Dale P. Conner Chapter 11 Gaps and Future Considerations for Development of Dermal Transdermal and Topical Delivery Systems Caroline Stransinger Chapter 12 Regulatory Challenges in Chemistry, Manufacturing and Controls: Gaps and Future Consideration for Locally Acting Topical Dermal Systems Shulin Ding Chapter 13 Development of Topical and Transdermal Dosage Forms: Regulatory Perspective Amit Mitra & Sarah A. Ibrahim Chapter 14 Innovations and Future Prospects of Dermal Delivery Systems Rashmi Upasani, Anushree Herwadkar, Neha Singh and Ajay K. Banga
OCLC-licensed vendor bibliographic record.
Keywords: MEDICAL / Dermatology; MEDICAL / Pharmacology; MEDICAL / Pharmacy; Transdermal medication; Drug delivery systems